Pathophysiological features of development of functional hypothalamic amenorrhea in patients with anorexia nervosa - G E Chernukha; D V Gusev; G I Tabeeva; V Yu Prilutskaia (IP Berlin A.V., 2018)
The energy deficit is the result of insufficient energy intake compared to its high costs. The development of energy deficiency is often associated with the desire to lose weight, a strict diet, as well as the woman's concern about her weight along with a change in eating behavior. The result of eating disorders in combination with a decrease in body weight is anorexia nervosa, accompanied by an energy deficit. Physiological changes occurring against a background of chronic energy deficiency contribute to the inclusion of compensatory mechanisms of energy conservation to provide vital physiological functions. The most frequent metabolic changes include hypoleptinemia in the presence of a decrease in the percentage of fat tissue, a decrease in triiodothyronine, and an increase in the concentrations of ghrelin, peptide YY and neuropeptide Y. The effect of energy and metabolic changes leads to suppression of the hypothalamic-pituitary-ovarian axis, gonadotropin releasing hormone secretion, with the subsequent suppression of the release of luteinizing and follicle stimulating hormones. The suppression of the hypothalamic-pituitary-ovarian axis leads to chronic estrogen deficiency, which is accompanied by the development of functional hypothalamic amenorrhea.